Content Validity and HOTS elements of Reading test items developed by MGMP teacher in Malang - Ghuzainu Nifiky Fiky (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This research presents the content validity and HOTS elements of reading comprehension test developed by MGMP teacher in Malang. The purpose of this study is to describe about the content validity based on basic competences and the HOTS usage of English reading comprehension test on semester assessment and final year assessment of 2018/2019 academic year. The total number of test items were 50 multiple choice items of semester assessment and 50 multiple choice items of final year assessment on seven grade. The method of this research used descriptive qualitative approach in which the researcher collecting the data by asking all assessments paper and syllabus to the school then the researcher analyzed the test items to find out the content validity and the use of HOTS elements. This research also categorized as descriptive analysis which also describes to what extent do the basic competences of Islamic Junior High School with its syllabus and the use of HOTS elements on these assessments. The finding of this research revealed that the test items of English reading comprehension test both on semester assessment and final year assessment had good content validity since it reached 0.94 of semester assessment and 0.96 of final year assessment, it can be concluded that the test items were covered basic competence then it had very high content validity according to Gregory, since it reached more than 0.80. Meanwhile the use of HOTS reached none elements of semester assessment and 15 elements of final year assessment. It can be concluded that there were 15 HOTS items out of 100 question items analyzed. It means that the use of HOTS both on English reading comprehension test both semester assessment and final year assessment were limited, since at Islamic Junior High School’s students should train in critical thinking. Keyword: basic competences, test items, HOTS